A Domain Analysis of the Influence of The Five Laws of Library Science - Martinez-Avila, Daniel; Almeida, Patricia de; Mira, Bianca Savegnago de [UNESP]; Gracio, Maria Claudia Cabrini [UNESP] (Natl Inst Science Communication-niscair, 2024)
The Five Laws of Library Science1is not only regarded as one of the most relevant and influential works by Shiyali Ramamrita Ranganathan, but also as a classic of the history of Library and Information Science. This book was the result of Ranganathan's search for a philosophical foundation of the area and also was the seed of much of his later legacy, as its objectives were developed and realised in some of his other most well-known works such as the Colon Classification, Classified Catalogue Code, Library Administration, and Prolegomena to Library Classification. The Five Laws of Library Scienceis the most cited work by Ranganathan according to the Google Scholar profile created by the Indian Documentation Research and Training Centre; moreover it has been translated into severallanguages and it is taught in library schools around the world. In this sense, complementing previous domain analyses of Ranganathan such as Smiraglia's2, based on the Web of Science, and inspired by the methodology of Guimar & atilde;es et al.3, who studied the influence of several works by Jesse Shera and Margaret Egan according to citations in Scopus, we conducted a search on the Web of Science Core Collection of all works citing Ranganathan. With the 306 citing documents, we conducted a domain analysis of the work mainly drawing on the bibliometric and epistemological approaches to characterise the domain of influence of The Five Laws of Library Science
Keywords: SR Ranganathan; The Five Laws of Library Science; Domain analysis